PEMANFAATAN EKSTRAK DAUN SELEDRI (Apium Graveolens) SEBAGAI ANTIKOAGULAN PENGGANTI EDTA (Ethylene Diamine Tetraacetic Acid) PADA PEMERIKSAAN JUMLAH TROMBOSIT - Ika Nurfajri Mentari; Desyani Ariza; Idham Halid (Politeknik Medica Farma Husada Mataram, 2020)
Celery (Apium Graveolens) has the same content as EDTA, namely flavonoids which can be used as anticoagulants, these flavonoids play a role in inhibiting the platelet aggregation process so that researchers want to do a research about of celery leaf extract (Apium Graveolens) as a substitute for EDTA (Ethylene Diamine Tetraacetic Acid) anticoagulants. Acid) on the examination of the platelet count. This research method is a laboratory experiment, namely the manufacture of celery leaf extract (Apium Graveolens) and homogenized with blood, which is then examined the number of platelets with 4 treatments. The examination of the platelet count also used the anticoagulant EDTA as a comparison. The results of examining the number of platelets using celery leaf extract with a concentration of 50% and using EDTA anticoagulants have the same results, so it can be stated that celery leaf extract can be used as an alternative anticoagulant as a substitute for EDTA (Ethylene Diamine Tetraacetic Acid) anticoagulant.